2004
DOI: 10.4028/www.scientific.net/msf.449-452.429
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Analysis of Plasma Induced in Laser Welding of Aluminum Alloys

Abstract: This paper describes the features and characteristics of plasma induced in the pulsed YAG laser welding of Al-Mg alloys in air and argon atmospheres. In the air environment, the identified spectra are atomic lines of Al, Mg, Cr, Mn, Fe and Zn, and singly ionized Mg line, as well as strong molecular spectrum of AlO, MgO and AlH. It has been confirmed that the resonant lines of Al and Mg were strongly self-absorbed. These facts have shown that the laser-induced plasma is relatively a low temperature and high den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
2
5
0
Order By: Relevance
“…10 13 cm -3 . Kim et al (2004) did a similar study and found similar results for even higher irradiations (~ 32 MW/ cm 2 ), namely the vapor/plasma temperature was very close to the boiling point of aluminium. Fig.…”
Section: Vapor/plasma Characterizationsupporting
confidence: 57%
“…10 13 cm -3 . Kim et al (2004) did a similar study and found similar results for even higher irradiations (~ 32 MW/ cm 2 ), namely the vapor/plasma temperature was very close to the boiling point of aluminium. Fig.…”
Section: Vapor/plasma Characterizationsupporting
confidence: 57%
“…To confirm the above finding, we reviewed available literature on the vapor/plasma temperature for Nd:YAG (similar wavelength as fiber laser) laser welding of aluminum alloys. Kim and Matsunawa (1996) used a pulse shapeable YAG laser with irradiations of up to 1 MW/cm 2 on 5000 series aluminum alloys and determined that the vapor/plasma plume was very weakly ionized, with approximate temperatures around 3280 K (barely above the vaporization temperature of aluminum) and electron densities of approximately 1.85 × 10 13 cm −3 . Kim et al (2004) did a similar study and found similar results for even higher irradiations (∼32 MW/cm 2 ), namely the vapor/plasma temperature was very close to the boiling point of aluminum.…”
Section: Vapor/plasma Characterizationmentioning
confidence: 99%
“…This difference in luminosity can be explained by a lower plume temperature of Al compared to Ti, determined by a lower absorptivity of the laser radiation (Table 1) and higher energy necessary to excite Al atoms, according to NIST database. 15 Kim and Matsunawa 17 reported the plume temperature barely above the boiling point for 5000 series aluminum alloys welded with Nd:YAG laser having an energy density of 1 MW/cm 2 . Kim et al 18 obtained the same result for an even higher energy density of 32 MW/cm 2 .…”
Section: Hsi Of the Vapor Plumementioning
confidence: 99%
“…15 Kim and Matsunawa 17 reported the plume temperature barely above the boiling point for 5000 series aluminum alloys welded with Nd:YAG laser having an energy density of 1 MW/cm 2 . Kim et al 18 obtained the same result for an even higher energy density of 32 MW/cm 2 . In the present experiments, the energy density was 9.5 MW/cm 2 , and taking into account close wavelengths of Yb:YAG and Nd:YAG laser, it can be supposed that the plume temperature should also near the boiling point of aluminum.…”
Section: Hsi Of the Vapor Plumementioning
confidence: 99%